Middle school cycling program is associated with improved mental health and wellbeing in adolescents during COVID-19 - Dementyev, Fletcher; Fish, Brian; Sakyi Opoku, Nana Yaa; Tesfaye, Lydia; Chan, Jason; Ortiz, Larry; Montgomery, Susanne B.; Walker, Esther J.; Wilson, Sean M. (Frontiers in Sports and Active Living, 2023)
The COVID-19 pandemic has exacerbated mental health issues among adolescents. Exercise is well-regarded for boosting mental health. Riding for Focus (R4F) is a 6-8 week cycling education program designed to equip middle school adolescents with basic cycling skills and introduce students to lifetime physical activity. A secondary goal of the R4F program is to improve adolescent mental health and psychosocial well-being. This study aimed to quantify the change in adolescent psychosocial well-being associated with the R4F program during the COVID-19 pandemic. Program evaluation also examined associations between participating in the R4F and mental health outcomes in the context of established risk factors, including gender, race, socioeconomic status, involvement in IEP programs, participation in after-school clubs, screen time, hours of sleep, and physical activity levels. Anonymous surveys were collected before and after the program in 20 schools in North America, with psychosocial well-being quantified using WHO-5 and PSC-17-Y. 1148 middle school students, aged 11-14, completed pre intervention surveys. 815 students also completed post intervention surveys. There was a general increase in psychosocial well-being after the R4F program and positive psychosocial well-being changes in students that identified as female, non-white, physically active, part of an IEP program, meeting screentime recommendations, and engaged in school programs, though effect sizes were small. Despite mental health improvements among underrepresented groups, relative risk assessments still indicated that males, white students, those from high socioeconomic status families still had reduced relative risk of developing psychosocial disorders post intervention. These analyses illustrate the feasibility of cycling as a viable PE elective and the need for further, more robust studies to better assess the positive impacts of the R4F scholastic cycling program on the psychological health and well-being of middle school age children.